Representasi Penyelenggaraan Pemilihan Umum Serentak Tahun 2024 dalam Prosedur Pemilu yang Bermutu dan Berintegritas - Tri Astuti; Nurika Falah Ilmania; Muhammad Muhibbin; Suratman Suratman (Jurnal USM Law Review)
This research article aims to describe the organization of general elections that represent elections with quality and integrity. In the 2024 simultaneous elections, the law used still refers to Law Number 7 of 2017 with several changes accommodated in the Constitutional Court Decision Number 114/PUU-XIX/2022. The implementation of simultaneous elections involves the General Election Commission (KPU), the Election Supervisory Body (Bawaslu), and the Election Organizer Honorary Council (DKPP). The quality and integrity of elections are not only influenced by these three central institutions, but also by the organizing committee in the field. This research article aims to describe the organization of general elections that represent elections with quality and integrity. In the 2024 simultaneous elections, the law used still refers to Law Number 7 of 2017 with several changes accommodated in the Constitutional Court Decision Number 114/PUU-XIX/2022. The implementation of simultaneous elections involves the General Election Commission (KPU), the Election Supervisory Body (Bawaslu), and the Election Organizer Honorary Council (DKPP). The quality and integrity of elections are not only influenced by these three central institutions, but also by the organizing committee in the field.